THE EFFECT OF HYPERTENSION GYMNASTICS ON LOWERING BLOOD PRESSURE IN THE ELDERLY - Mua, Estelle Lilian; Sekeon, Robi Adikari; Anggreyni, Meilin; Purwiningsih, Sri; Ito, Kirey Sintisye Putri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Hypertension in the elderly in Central Sulawesi Province as of 2019 was 213,686 people. Hypertension exercise is effective in decrease hypertension in the elderly. The purpose of this study was to determine the effect of hypertension exercise on systolic and diastolic blood pressure in the elderly who suffer from hypertension. This research is descriptive-quantitative with a pre-experimental design using one group time series design (Pre-Test and Post-Test), at the Tresna Werdha Tentena Social Institution, July 2020. The population is 63 and The sample is 15 elderly people. Data analysis used the one-sample dependent t-test. The results of the analysis of research data that the blood pressure of the elderly in the systolic pretest obtained a systolic t value of 4.08 and a diastolic value of 1.57, with acceptance criteria (t > 2.14), then the systolic value means that Ho is rejected, meaning that there is a difference between pretest and post-test, As for the diastolic value, Ho is accepted, meaning that there is no difference between the pre-test and post-test. The conclusion is that elderly hypertension exercise is quite effective for controlling hypertension in the elderly, especially for reducing the level of systolic blood pressure in the elderly, if it is carried out regularly and is controlled and sustained, while for diastolic blood pressure, the level of effectiveness obtained is unknown.